Single-step chromatographic isolation of lithium from whole-rock carbonate and clay for isotopic analysis with multi-collector ICP-mass spectrometry. Issue 12 (27th October 2015) - Van Hoecke, K.; Belza, J.; Croymans, T.; Misra, S.; Claeys, P.; Vanhaecke, F.
Abstract : An ion chromatographic procedure allows isolation of lithium from carbonate and clay material prior to isotope ratio determination with MC-ICP-MS. Abstract : Lithium isotope ratios play a key role in tracing weathering processes within the context of paleoclimatologic research. Therefore, accurate and precise determination of the isotopic composition of Li is required for a large variety of complex geological samples with widely different Li contents. This technical note describes the extension and fine-tuning of the existing cation exchange chromatographic procedures for isolation of Li to whole-rock carbonate and clay matrices prior to its isotopic analysis via multi-collector ICP-mass spectrometry. The method developed permits the isolation of ≥20 ng amounts of Li from carbonates and clays, by using a 25 cm long cylindrical column loaded with 8 and 2 mL of AG-50W-X8 cation exchange resin, respectively. A 0.5 M HCl solution is used as eluent. Li recoveries ≥99% were achieved and isotopic analysis using 10–20 ng of isolated Li resulted in accurate and precise δ 7 Li values – external precision (2SE) of 0.2‰ ( N = 15). The analytical procedures developed allow Li isotope ratios to be investigated in parallel in both the clay and carbonate fractions of a geological sample within the context of paleoclimatological research.